Небесные сполохи и земные заботы - Алексеева Лилия Михайловна (Наука и прогресс, 1985)
Экземпляры: (20221026) / Инвентарный номер: 12729 / Цена: 0.25 / Сис.шифр: 26.23 / Авт.знак: А 47 / ГРНТИ: 37.21 / ББК: 26.23